Study of Relationship between Pyrethroid Structure and Resistance in Cotton Bollworm Helicoverpa armigera (Hubner) - Shinde3 and Muley S.P.3, Nimbalkar R.K.1*, Wadikar M.S.2, S.S. (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: Arial; mso-ansi-language: EN-US;">Resistance of insects to insecticides continues to be a serious barrier to successful management of insect pests. Field populations of Helicoverpa armigera have developed resistance to every class of insecticide over the past 40 years. Insects can develop resistance through reduced target site sensitivity, enhanced metabolism and decreased penetration. In the present study, the degree to which cross-resistance is conferred between Ops and pyrethroids by selection for enhanced esterase activities were examined. Resistance was highest to the insecticide used for selection In addition; pyrethroid resistance was higher to insecticides with 3-phenoxybenzyl alcohol/aldehyde, negative cross-resistance was not measured for either acephate or indoxacarb. In contrast, high levels of cross-<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US;"> <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: Arial; mso-ansi-language: EN-US;">resistance to indoxacarb existed in both OP-R (RR: 15.8) and PYR-R (RR: 5.57) strains,Â  a low level of resistance to spinosyn A was measured in OP-R (RR: 2.19) and PYR-R (RR: 2.99) larvae. The present studies suggest that the chemical structure of an insecticide is an important determinant of metabolism and cross-resistance. The objective of this study was to investigate the relationship between pyrethroid structure and cross-resistance in Helicoverpa armigera.